2015
DOI: 10.1038/bjc.2015.367
|View full text |Cite
|
Sign up to set email alerts
|

FAT4 functions as a tumour suppressor in gastric cancer by modulating Wnt/β-catenin signalling

Abstract: Background:FAT4, a cadherin-related protein, was shown to function as a tumour suppressor; however, its role in human gastric cancer remains largely unknown. Here, we investigated the role of FAT4 in gastric cancer and examined the underlying molecular mechanisms.Methods:The expression of FAT4 was evaluated by immunohistochemistry, western blotting, and qRT–PCR in relation to the clinicopathological characteristics of gastric cancer patients. The effects of FAT4 silencing on cell proliferation, migration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 42 publications
14
66
0
1
Order By: Relevance
“…In addition, upregulating FAT4 could inhibit the GC cells proliferation and suppress the growth of xenograft tumor in nude mice, which was similar to the results of down-regulating miR-107. Cai et al 29 demonstrated that down-regulation of FAT4 could promote the growth, EMT of GC cells via activation of Wnt/βactin signaling. EMT is an vital mechanism of tumor cell invasion and metastasis, with the declining of E-cadherin and increasing of N-cadherin, vimentin in its process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, upregulating FAT4 could inhibit the GC cells proliferation and suppress the growth of xenograft tumor in nude mice, which was similar to the results of down-regulating miR-107. Cai et al 29 demonstrated that down-regulation of FAT4 could promote the growth, EMT of GC cells via activation of Wnt/βactin signaling. EMT is an vital mechanism of tumor cell invasion and metastasis, with the declining of E-cadherin and increasing of N-cadherin, vimentin in its process.…”
Section: Discussionmentioning
confidence: 99%
“…When Wnt signal pathway is activated by the stimuli to cells, Wnt ligand, binding with the Frizzled/LRP receptor, can activate the Dsh through phosphorylation, thereby isolating the β-catenin from APC/Ax -in/GSK-3β; the accumulation of β-catenin would further enter the nuclear to combine with the TCF/LEF complex, thereby activating the transcription of downstream target genes, through which Wnt signal pathway can regulate various biological events, like cell proliferation, apoptosis, mobility and differentiation [20,21]. Research has reported the close correlations of β-catenin with the development and progression of a variety of tumors, including liver cancer [22], gastric cancer [23] and lung cancer [24]. All these studies have shown that β-catenin is highly expressed in the above tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis indicated that these candidates may have a putative role in development or progression of human lung cancer. Moreover, some of these of the candidates, such as DLC1 (36), FAT4 (37), and FAS (28), are well-known tumor suppressors.…”
Section: Transcriptome Analysis Of Kras Knockout Cells Revealed Distimentioning
confidence: 99%